Uji Antiinflamasi Ekstrak Etanol Ashitaba (Angelica keiskei) Secara In Vitro - Fitriana, Mariama; Hajrin, Wahida; Subaidah, Windah Anugrah; Ridwan, Sucilawaty; Pratiwi, Eskarani Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Angelica keiskei has potential as an anti-inflammatory agent because it contains chalcone which has been proven to be able to suppress inflammation through inhibiting nitric oxide production and inhibiting the expression of the iNOS and COX-2. The anti-inflammatory potential of Angelica keiskei needs to be tested. This study aimed to determine the anti-inflammatory activity of Angelica keiskei ethanol extract using the protein denaturation inhibition method. Angelica keiskei was extracted using the sonication method with 96% ethanol. The extract was tested for anti-inflammatory activity using the protein denaturation inhibition method with diclofenac sodium as a positive control. The percent of inflammatory inhibition is used to assess sample activity. The results showed that the percent of inflammatory inhibition of Angelica keiskei ethanol extract increased as the test concentration increased. The maximum percent inhibition was obtained at a concentration of 1.5% with the percent of inflammatory inhibition value of 23.14% ± 0.05. Angelica keiskei ethanol extract has anti-inflammatory activity based on in vitro testing using the protein denaturation inhibition method.